TEKNIK PEMERIKSAAN DAN PERBAIKAN INSTALASI PIPA GALVANIS - Abdillah, Rifqi Aulia; Setiawan, Dedi Budi; Supriyo, Supriyo; Ariyanto, Arief Subakti; Pamungkas, Nur Setiaji (Politeknik Negeri Semarang, 2024)
The plumbing system must be able to anticipate pollution from outside, So damage to pipes must be minimized because if there is a leak in the pipe it will not only affect water distribution but can also cause the water to be contaminated with dirt. Research needs to be carried out regarding inspection methods and techniques for repairing leaks in pipe installations so that if the installation experiences a leak it can be repaired immediately. The method used in this research is an experimental method, namely modeling a water pipe installation that has a leak, then applying inspection techniques and repair techniques to the pipe installation. Based on water discharge measurements carried out during 1 minute of water flow in pipe installations in normal conditions with pipes experiencing leaks, there was a decrease in water discharge of 39.023 liters/minute. To find out the leak point, it is necessary to carry out a further inspection using a pipe leak listening device. The results of the inspection carried out three times with different people showed that the inspection results shifted from the leak point by a maximum of 10 mm. Based on the research results, it was found that a repair technique that can be applied to leaks in galvanized pipe installations is strengthening with pipe clamps capable of withstanding a pressure of 1.2 Mpa with an implementation cost of Rp. 277,500.00, and the welded reinforcement is able to withstand a pressure of 3.4 Mpa with an implementation cost of Rp. 463,458.00. So the inspection method of measuring flow and checking with a listening device can be applied to check leak points in pipe installations, while the most appropriate method for repairing leaks in galvanized pipe installations is to use pipe clamp reinforcement, because it obtains a compressive strength that meets the minimum pressure requirements in pipe installations. residential house and in terms of costs it is cheaper than using welding reinforcement techniques.